Giant optical anisotropy in transition metal dichalcogenides for next-generation photonics - G. A. Ermolaev (Nature Portfolio, 2021)
Optical anisotropy in a broad spectral range is pivotal to efficient light manipulation. Here, the authors measure a birefringence of 1.5 in the infrared range and 3 in the visible light for MoS2.